ONTOLOGI, EPISTEMOLOGI, DAN AKSIOLOGI SERTA AKTUALISASINYA DALAM STUDI TAFSIR - Basyir, Djazuli Ruhan (Institut PTIQ Jakarta, 2024)
The purpose of this study is to develop a framework of thought regarding ontology, epistemology, and axiology in the interpretation of the Qur'an through a systematic approach in the philosophy of science. This study aims to identify, analyze, and construct a more comprehensive understanding of the three concepts, so that they can form a methodological basis that is relevant to the context of the interpretation of the Qur'an. By using the library study method, this study utilizes primary data from the main literature on the philosophy of science and 'Ulum al-Qur'an, as well as secondary data from journal articles and relevant academic documents. Primary data provides a strong conceptual foundation, while secondary data complements the analytical perspective by adding an applied context. This study highlights how ontology, epistemology, and axiology play a role as pillars in the formation of an interpretation methodology that is not only theoretical, but also applied. As a result, this study offers that through the systematics of ontology, epistemology, and axiology as a framework in a more holistic study of interpretation, it is able to answer modern challenges with relevance and depth, and contribute to the development of the method of interpretation of the Qur'an that integrates philosophical values in contemporary interpretation practices.